2001
DOI: 10.1021/jm991128y
|View full text |Cite
|
Sign up to set email alerts
|

C-Isoprenylation of Flavonoids Enhances Binding Affinity toward P-Glycoprotein and Modulation of Cancer Cell Chemoresistance

Abstract: Previous studies have shown that flavones bind to P-glycoprotein (Pgp) with higher affinity than isoflavones, flavanones, and glycosylated derivatives. In the present work, a series of C- or O-substituted hydrophobic derivatives of chrysin were synthesized to further investigate structural requirements of the A ring toward Pgp modulation. Increasing hydrophobicity at either position 6, 8, or 7 increased the affinity of in vitro binding to a purified cytosolic domain of Pgp, but only benzyl and 3,3-dimethylally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
93
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(97 citation statements)
references
References 19 publications
3
93
1
Order By: Relevance
“…Mitoxantrone and rhodamine 6G were purchased from Sigma (L'isle d'Abeau, Chesnes, France), and nonprenylated flavonoids from Extrasynthèse (Genay, France). Prenylated derivatives of chrysin were obtained as previously described (15,28). GF120918 was provided by GlaxoSmithKline (Madrid, Spain).…”
Section: Methodsmentioning
confidence: 99%
“…Mitoxantrone and rhodamine 6G were purchased from Sigma (L'isle d'Abeau, Chesnes, France), and nonprenylated flavonoids from Extrasynthèse (Genay, France). Prenylated derivatives of chrysin were obtained as previously described (15,28). GF120918 was provided by GlaxoSmithKline (Madrid, Spain).…”
Section: Methodsmentioning
confidence: 99%
“…We have studied flavones, flavonols, chalcones and other phenolic compounds, and have identified the structural criteria required for a high binding-affinity. [9][10][11][12][13] Continuing our efforts in identifying Pgp-mediated MDR modulators, we wish to report here for the first time the binding of aurones, which constitute a naturally-occurring subclass of flavonoids frequently found in plants, where they contribute to the coloration of fruits and flowers (Fig. 1).…”
mentioning
confidence: 99%
“…Park et al (14) indicated that 6,8-disubstituted chrysin derivatives, which were obtained from naturally occurring ChR by halogenation, showed as strong an inhibitory activation of PGE2 production from LPS-induced RAW 264.7 cells as wogonin, a well-known natural flavone that has strong and selective COX-2 inhibitory activity. Comte et al (15) reported that through alkylation, the hydrophobic degree of ChR is increased, the KD value is decreased and the binding affinity toward P-glycoprotein (P-gp) in the cell is enhanced. We previously showed that 5,7-dihydroxy-8-nitrochrysin (NOC) was obtained through synthesization (16).…”
Section: Introductionmentioning
confidence: 99%